Computational analysis on performance of thermal energy storage (TES) diffuser - Mohd Azrul Hisham, Mohd Adib; A. R., Ismail; F., Adnan; K., Kadirgama; H. A., Salaam; Zulkifli, Ahmad@Manap; Nasrul Hadi, Johari; Zulfika, Anuar; N. S. N., Azmi (IOP Publishing, 2012)
Application of thermal energy storage (TES) system reduces cost and energy consumption. The performance of the overall operation is affected by diffuser design. In this study, computational analysis is used to determine the thermocline thickness. Three dimensional simulations with different tank height-to-diameter ratio (HD), diffuser opening and the effect of difference number of diffuser holes are investigated. Medium HD tanks simulations with double ring octagonal diffuser show good thermocline behavior and clear distinction between warm and cold water. The result show, the best performance of thermocline thickness during 50% time charging occur in medium tank with height-to-diameter ratio of 4.0 and double ring octagonal diffuser with 48 holes (9mm opening ~ 60%) acceptable compared to diffuser with 6mm ~ 40% and 12mm ~ 80% opening. The conclusion is computational analysis method are very useful in the study on performance of thermal energy storage (TES).